2011
DOI: 10.1007/s11172-011-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic agents based on diterpenoid alkaloids

Abstract: Diterpenoid alkaloids comprise a large group of natural compounds produced by the plants of the genera Aconitum and Delphinium. Some of these compounds were found to manifest valuable pharmacological properties, including the unique antiarrhythmic activity. Allapinine (derived from the alkaloid lappaconitine) was approved as a drug. The investigation of the structure-activity relationship revealed structural elements responsible for the arrhythmogenic and antiarrhythmic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…7 DTAs as well as LC, isolated from the plants of genera Aconitum, comprise a large group of antiarrhythmic and arrhythmogenic agents. 8 So, one of the arrhythmogenic agents, aconitine, a site 2 sodium channel neurotoxin, induces severe neurological symptoms and cardiovascular collapse. 9 This is even more interesting because studies at the cellular level have shown that LC and aconitine bind to the sodium channels in a similar way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 DTAs as well as LC, isolated from the plants of genera Aconitum, comprise a large group of antiarrhythmic and arrhythmogenic agents. 8 So, one of the arrhythmogenic agents, aconitine, a site 2 sodium channel neurotoxin, induces severe neurological symptoms and cardiovascular collapse. 9 This is even more interesting because studies at the cellular level have shown that LC and aconitine bind to the sodium channels in a similar way.…”
Section: Introductionmentioning
confidence: 99%
“…9 Attempts to trace the "structure-property" relationship of a few DTAs have been made in a review. 8 The principal problems in establishing any regularity arise from the fact that DTAs, both antiarrhythmic and arrhythmogenic, contain almost the same set of substituents, viz., there are one ethyl group at the nitrogen atom in the DTA fragment, several hydroxy and methoxy groups, and one aromatic substituent. The latter is the fragment of benzoic or anthranilic acid (AA).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, among diterpene alkaloids there are compounds with opposite, antiarrhythmic activity. Napelline (8) showed to exert low antiarrhythmic activity in rats [31], while delavaconitine (2) inhibited aconitine-induced arrhythmia Acta Biologica Hungarica 68, 2017 [21]. In vitro study revealed the activity of acontine (3) and hetisione (9) on Na v 1.2 sodium channel.…”
Section: Introductionmentioning
confidence: 99%
“…puberulum and A. sinomontanum (De-Quan and Das, 1983;Mu et al, 2012;Shafikova et al, 2008;Sun et al, 2009a, b, c). Since lappaconitine was extracted, it has exhibited a wide range of biological activities (Ahmad et al, 2008;Dzhakhangirov et al, 2007;Tolstikova et al, 2007Tolstikova et al, , 2009Turabekova et al, 2008); for example, the form of hydrobromide (the compounds of other salt forms are not reported yet) has been widely used in clinical for treatment of neuropathic pain as a non-addictive drug in China (Ou et al, 2011;Wang et al, 2009a, b) and as an antiarrhythmic in Uzbekistan (Yunusov, 2011). However, analgesic effect was hampered due to the low efficiency in clinical (Sun et al, 2011a(Sun et al, , b, 2012(Sun et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%